2018
DOI: 10.1159/000489939
|View full text |Cite
|
Sign up to set email alerts
|

Jumping Breast Phenomenon Following Subcutaneous Mastectomy: First Description and Grading of a Well-Known Breast Deformity

Abstract: Introduction: One of the goals of breast cancer surgery is to preserve the breast. However, where this is not possible, various breast reconstructive procedures are available. The most common procedure is the immediate insertion of a subpectoral implant after removing the breast tissue. A significant challenge involving subpectoral implants is the deformation of the breast upon contraction of the pectoral muscle causing elevation of the breast and development of wrinkles or ripples in the caudal and cranial qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…Several methods have been proposed to assess BAD [3,7,10, 20,21]. Most recently, Fracol et al [21] suggested using Kim’s quantitative grading scale to standardize the grading of BAD by nipple displacement in centimeters and the percentage of skin area affected by rippling [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several methods have been proposed to assess BAD [3,7,10, 20,21]. Most recently, Fracol et al [21] suggested using Kim’s quantitative grading scale to standardize the grading of BAD by nipple displacement in centimeters and the percentage of skin area affected by rippling [21].…”
Section: Discussionmentioning
confidence: 99%
“…Landmarks on the breast were marked and analyzed on still photos with and without contraction of the PMM. In addition, Kummel et al [10] proposed a more detailed 3-point grading system to describe and distinguish grades of BAD in women undergoing augmentation and suggested how to prevent BAD by performing a two-stage procedure. Furthermore, Vidya and colleagues suggested how to manage BAD in relation to its grading for women undergoing subpectoral reconstruction [7].…”
Section: Table 4 Intra-and Inter-rater Agreement Using the Nse Gradin...mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last years, there has been increased focus on BAD and several studies have been conducted to assess the etiology, treatment, and grading. 3 13 22 23 24 This randomized controlled trial is, to the best of our knowledge, the first evaluating and comparing sub- and prepectoral implant placement when performing direct-to-implant breast reconstruction. We found a significant difference in the incidence and degree of BAD between sub- and prepectorally reconstructed groups when evaluating the patients by the NSE grading scale 12 months after surgery ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…This change however, gives a resurgence of potential problems such as thin tissue coverage allowing visible implant edges, secondary ptosis and possibly increased rates of capsular contracture. These are potential risks, which needs to be examined in future studies (5,6). The aim of this visualized surgery paper was to visualize and highlight the technical disparities between a sub-and prepectoral direct to implant breast reconstructive techniques applied at our institutions.…”
Section: Introductionmentioning
confidence: 99%